PENGEMBANGAN KUIS INTERAKTIF DENGAN CLASSPOINT BERBASIS KURIKULUM MERDEKA PADA MATA PELAJARAN EKONOMI - Rahayu, Riska; Andayani , Endah; Mardiana, Riril (Jurnal Penelitian dan Pendidikan IPS, 2024)
The aim of this research is to determine the process of developing interactive quizzes with classpoints based on the independent curriculum in class X economics subjects at SMA Negeri 6 Malang and to analyze their feasibility. Research using the ADDIE model research and development (R&D) approach with 5 stages is the focus of the research, namely; (1) analysis, (2) design, (3) development, (4) Implementation (5) Evaluation. The results of the feasibility validation from the three validators are as follows; (1) material expert validation obtained 92.5% with a very feasible category with the advantage of being able to change the material and add material for example market structure material, (2) media expert validation obtained 95% with a very feasible category with the advantage of classpoint which has many features so that it can making learning interactive and active, (3) language expert validation obtained 90% in the very appropriate category with the advantage that the language used is very easy to understand, (4) and expert student responses received 92.71% in the very appropriate category. Â  Â